Analysis of Fire Protection System Requirements in Onshore Oil and Gas Exploration and Production Gathering Stations - Bening Pahli, Joewan; Dharmastiti, Rini (CV. Publikasi Indonesia, 2026)
This research aims to evaluate and analyze the technical requirements of the fire protection system at the facility to ensure compliance with international safety standards and actual field conditions. The theoretical framework and evaluation instruments are based on National Fire Protection Association (NFPA) standards, including NFPA 11 (Foam Systems), NFPA 15 (Water Spray Fixed Systems for Fire Protection), NFPA 20 (Installation of Stationary Pumps for Fire Protection), and NFPA 2001 (Clean Agent Fire Extinguishing Systems), as well as standards from the American Petroleum Institute (API), such as API 2030 and API RP 2001. The research methodology uses an applied case study with a quantitative technical approach, consisting of field data collection, fire zone classification, determination of worst-case fire scenarios, and hydraulic calculations for water, foam, and pump pressure requirements. The analysis classifies the M-8 Gathering Station into eight fire zones, with Fire Zone 1 (Crude Oil Storage Tank Area) identified as the critical design case, having the highest fire-water demand of 1,195 GPM. The infrastructure analysis shows that the water pond capacity of 1,386 m³ and foam tank capacity of 5,151 liters are sufficient to meet a four-hour operational requirement. Hydraulic analysis indicates a required pump discharge pressure of 132.43 psig to ensure effective fire suppression. The study concludes that the designed fire protection system meets safety standards and recommends the installation of appropriate nozzles and clean agent systems to enhance fire safety and operational reliability at Gathering Station M-8.